Antivirotics based on defective interfering particles: emerging concepts and challenges - Maryanchik, S. V.; Borovikova, S. E.; Ivanova, A. O.; Trofimov, V. V.; Bagrova, O. E.; Frolova, A. S.; Mityaeva, O. N.; Volchkov, P. Yu; Deviatkin, A. A. (Frontiers in Cellular and Infection Microbiology, 2025)
Viruses are obligate parasites, that use the host’s internal metabolic systems for their own reproduction. This complicates the search for molecular targets to prevent the spread of viral infection without disrupting the vital functions of human cells. Defective interfering particles (DIPs) are natural competitors of viruses for important resources of viral reproduction. DIPs emerge during infection, originate from the normal viral replication process and inhibit its progression, making them an interesting candidate for antiviral therapy. Here we describe the biology of DIPs, advances in DIP-based antiviral technology, analyze their therapeutic potential and provide a systemic overview of existing preventive and therapeutic antiviral strategies.